Reconstructive Endovascular Treatment of Basilar Trunk and Vertebrobasilar Junction Aneurysms: A Review of 77 Consecutive Cases - Peng, Qichen; Zhou, Yangyang; Li, Wenqiang; Wang, Chao; Dong, Linggen; Mu, Shiqing; Zhang, Yisen (Frontiers in Neurology, 2022)
Background Basilar trunk and vertebrobasilar junction (BTVBJ) aneurysms have a poor prognosis and are challenging to treat. Objective This study aimed to evaluate the efficacy of reconstructive endovascular treatment for BTVBJ aneurysms and explore a treatment selection paradigm. Methods Clinical and angiographic data from 77 patients with 80 BTVBJ aneurysms who underwent endovascular treatment with flow diverters (FDs) or conventional stent-assisted coiling between January 2016 and December 2020 were retrospectively analyzed. Aneurysm characteristics and treatment outcomes were compared between treatment groups. Results Among the 77 study patients, 34 (44.2%) were treated with FDs and 43 (55.8%) with conventional stent-assisted coiling. Overall, 72.7% of patients achieved favorable clinical outcome at follow-up. The rate of procedure-related complications was 23.4%. The aneurysm occlusion rate at last follow-up did not differ between the FD and conventional stent groups (79.2% vs. 77.1%, p = 0.854). Although the occlusion rate immediately after the procedure was lower in the FD group (29.4%), incidence of progressive occlusion was significantly higher (62.5 vs. 5.7%; p < 0.001). The proportion of patients with large and giant aneurysms (≥10 mm) was significantly higher in the FD group (70.6 vs. 34.8%; p = 0.002). In patients with large or giant aneurysms, favorable clinical outcome at last follow-up was achieved in 75% of patients in the FD group but only 43.8% of patients in the conventional stent group (p = 0.046). Moreover, the complication rate was lower in the FD group, but the difference was not significant (20.8 vs. 37.5%; p = 0.247). The same analyses were performed for patients with small aneurysms (<10 mm) but no significant differences between the two groups were observed. Conclusion Endovascular treatment of small BTVBJ aneurysms using either FDs or conventional stents was feasible and effective. In patients with large or giant aneurysms, treatment using FDs achieved higher rates of occlusion and favorable clinical outcome at last follow-up than conventional stent-assisted coiling.